Instant thyroid crisis of autonomously functioning thyroid nodule after radio frequency ablation and ethanol injection - Ladan Mostafavi; Iraj Heydari; Maryam Farasatinasab; Hossein Chegeni; Hojat Ebrahiminik; Jeyran Zebardast; Ramin Malboosbaf (Journal of Clinical and Translational Endocrinology Case Reports, 2023)
Radiofrequency ablation (RFA) is acknowledged as an effective and safe technique for the treatment of benign thyroid nodules. However, recently there have been some reports of thyroid dysfunction related to this technique, especially thyrotoxicosis. Here, we report a case of a 34-year-old woman's thyroid crisis instantly (about 20 minutes) after RFA and ethanol injection for an autonomous functional thyroid nodule. Fortunately, her symptoms improved with treatment (hydration, corticosteroid, propylthiouracil, and propranolol), and after three days, she was discharged from the hospital in good condition.